Pemetaan Objek Wisata Bahari Kabupaten Kepulauan Selayar Berbasis Sistem Informasi Geografi - Muhammadiyah, Ali Rahmat (UNIVERSITAS NEGERI MAKASSAR, 2018)
The purpose of this study was to determine (1) how the management of marine tourism objects carried out by the Selayar Islands Regency government; (2) How to map the Selayar Islands Regency marine tourism object based on geographic information systems. This type of research is qualitative with descriptive method. Data collection techniques used in this study are observation techniques, field measurement techniques, interview techniques and documentation techniques in collecting data. The results of this study are (1) Management of the Selayar Islands Regency marine tourism object is a management that in addition to paying attention to the preservation aspect also provides participation to the community as planners, implementers and managers of marine tourism objects. Not yet formed a tourism conscious society as a whole causes planning, implementation up to the management of marine tourism objects is not optimal; (2) There are 38 marine tourism objects in Selayar Islands Regency, 22 of them have been studied and 16 others have not been studied.